Concordance between clinical and histopathologic diagnosis and an audit of oral histopathology service at a Nigerian tertiary hospital - Soyele, Olujide Oladele (Pan Afr Med J, 2019)
INTRODUCTION: Although histopathological diagnosis remains the gold standard; good clinical impression is potentially a key diagnostic tool in rural resource-limited settings. Thus, good concordance between clinical impression and histopathological diagnosis is thus a very crucial diagnostic oral pathology tool in low- and middle-income countries (LMICs). METHODS: This retrospective study was performed at the Oral pathology and Oral diagnoses units of Obafemi Awolowo University Teaching Hospital Complex (OAUTHC), Osun state. Clinicopathological reports of all biopsies between the period of 2008-2017 were retrieved and analyzed. Descriptive analysis of data was done using Stata 14. Frequency of oral lesions and rates of accurate clinical diagnoses were evaluated for lesional sites and clinician's qualification/specialization. RESULTS: In 592 biopsied cases, the mean age was 36.1years with higher female predilection (54.4%). Odontogenic tumors (OTs) were the most prevalent category of lesions (25.3%, n=149), followed by reactive lesions (12%, n=71). Absolute concordance was recorded for 54.6% (k=0.5) of the cases; with highest concordance observed in fibro-osseous lesions (65.6%, k=0.43), and least in pulp/periapical lesions (3.5%). Concordance was higher in females (59.5%, k=0.53) than males (48.3%, k=0.44). Oral medicine specialists had the highest concordance index (62.5%, k=0.59). CONCLUSION: The findings in this research indicate that, on a general note, the degree of concordance between clinical and histopathological diagnosis is poor. Hence, improvement in diagnostic skills (irrespective of clinical specialty) is important to improve treatment outcomes, particularly in LMICs. Continuous personnel training and utilization of advanced diagnostic techniques can potentially help bridge the diagnostic gaps.